2020
DOI: 10.7759/cureus.11293
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis and Serotonin: Potential Therapeutic Applications

Abstract: Multiple sclerosis (MS) is a neurodegenerative disease with a complex autoimmune component, and it has a high prevalence among middle-aged females. The manifestations of the disease range from episodic somatosensory dysfunction to progressive and permanent central nervous system (CNS) damage. Due to a high prevalence of psychiatric comorbidities and proven abnormalities in serotonin (5-HT) levels among MS patients, they are usually on drugs that modify the serotonergic system. Through a comprehensive literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The neuroprotective role of serotonin [ 3 ] is associated with its ability to modulate the inflammatory response of lymphocytes [ 6 ] involved in MS disease course [ 15 ], but the knowledge of the receptors involved is limited. Moreover, several studies reported an important activation of immune cells in peripheral blood from MS patients, including changes in surface phenotype [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The neuroprotective role of serotonin [ 3 ] is associated with its ability to modulate the inflammatory response of lymphocytes [ 6 ] involved in MS disease course [ 15 ], but the knowledge of the receptors involved is limited. Moreover, several studies reported an important activation of immune cells in peripheral blood from MS patients, including changes in surface phenotype [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, 5-HT was shown to play an immune-modulatory role in the pathogenesis of autoimmune diseases such as multiple sclerosis (MS) [ 3 ], without understanding precisely the molecular events involved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older humans also have increased numbers of enterochromaffin cells (Yu et al, 2016 ), which secrete the hallmark hormone serotonin. Altered levels of and signaling by serotonin play a role in a variety of neurodegenerative disorders including Parkinson's disease (Fox et al, 2009 ; Politis & Niccolini, 2015 ), multiple sclerosis (Malinova et al, 2018 ; San Hernandez et al, 2020 ), and Alzheimer's disease (Mdawar et al, 2020 ; Smith et al, 2017 ). The impact of aging on enteroendocrine cells remains understudied but given the role of this IEC subtype in the sensing of and response to luminal contents and the microbiota, and their systemic effects, these cells may represent major players in the regulation of aging process and age‐associated comorbidities.…”
Section: Intestinal Epithelial Cell Populations During the Aging Processmentioning
confidence: 99%
“…Activation [ 54,55] ERK1/2 activation promotes OL differentiation and myelination, [56] enhances microglial and astroglial activation, presumably augmenting neuroinflammation, [57] promotes neuronal survival or death in a context-dependent manner [ 55,58] Neurotransmitter serotonin (5-HT) Activation [59] Serotonin levels are diminished in MS patients/5-HT may exert immunosuppressive and neuroprotective effects [60] Tumor necrotic factor alpha (TNF𝛼) Activation [61] Tumour necrosis factor alpha (TNF𝛼), upregulated in MS patients and animal models, is required for oligodendroglial remyelination, [62] regulates neuroinflammation, [63] and exerts neuroprotection [64] Neuronal activity, molecularly mediated by phospholipase C (PLC) and calmodulin-dependent kinase II (CaMKII)…”
Section: Upstream Modulators Parp1 Modulation Possible Implications O...mentioning
confidence: 99%